An algorithm to model wood accounting for different tension and compression elastic and failure behaviors. (15th June 2016) - Iraola, B.; Cabrero, J.M.
Highlights: A direction dependent algorithm to model wood in FEA is proposed. Different material properties are automatically applied for tension and compression. The algorithm allows the use of different failure criteria for each tensional state. Different progressive damage models are employed according to the detected failure. Good agreement has been found between simulations and different test types. Abstract: Wood, as a natural heterogeneous material, is a challenging material to simulate. This work presents an algorithm to model both its elastic and post-elastic responses. It allows to model different compression and tension elastic and failure behaviors in both material directions, parallel and perpendicular to the grain. It employs two different strategies: a sequential application of different failure criteria, and the modeling of post-elastic response by means of damage and stress reduction parameters. The proposed algorithm is applied to spruce in two experimental cases with different loadings and failure modes. When reasonable mesh density and increment size are used, the obtained results are in good agreement with the experimental results. The proposed algorithm has been programmed in the commercial software ABAQUS. However, it may be easily applied to different platforms or wood species.